Human capacity building through the recognition of prior learning : implications for higher education - Kaur, Kuldip; Nirwan Idrus (2009)
The conviction that education is fundamental to employment, and that productive employment is central to improved livelihood, underlies several global initiatives. In order to enhance enterprise competence among the employed workforce, and to cater for the human resource needs in a country, education must respond to global changes and economic developments (Gopinathan, 2005). To support the growing need for human capacity building, such a response would include lifelong education, formal and nonformal education and training, as well as inter-institution collaboration. Central to this perspective is the recognition of prior learning (RPL), that is, the acknowledgement of competencies accrued through worklife skills, experiential learning and non-formal training against academic learning outcomes and competence standards. However, given the traditionalist posture taken by most Malaysian institutions of higher education, an emerging issue with regards to the provision of prior learning credit through RPL is ensuring institutional capacity in prior learning assessment and the provision of learning support for students wishing to express prior learning for RPL. This paper discusses a number of issues related to the implementation of RPL, as well as to the mechanisms used to harness the competence, experience and abilities of employed adults seeking further education.